2018
DOI: 10.1111/ejn.13795
|View full text |Cite
|
Sign up to set email alerts
|

The locus coeruleus–norepinephrine system as pacemaker of attention – a developmental mechanism of derailed attentional function in autism spectrum disorder

Abstract: Children with autism spectrum disorder (ASD) exhibit diminished visual engagement to environmental stimuli. Aberrant attentional function provides an explanation by reduced phasic alerting and orienting to exogenous stimuli. We review aberrant attentional function (alerting, orienting and attentional control) in children with ASD as studied by neurocognitive and neurophysiological tasks as well as magnetic resonance imaging studies. The locus coeruleus-norepinephrine (LC-NE) system is outlined as a pacemaker o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 171 publications
(249 reference statements)
3
75
0
Order By: Relevance
“…In both cases, these effects remained sustained for entire duration of the target period. In a recent investigation run with the Attention Network Task (Petersen and Posner, ) to explore the alerting, orienting and executive‐control components of attention (for a review on the relationship of these components with LC‐NE activity, see Bast et al., ), Geva et al. () have described PDil effects related to the attentional and control components of attention that have onset latencies similar to those of the PDil effects observed in our study.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In both cases, these effects remained sustained for entire duration of the target period. In a recent investigation run with the Attention Network Task (Petersen and Posner, ) to explore the alerting, orienting and executive‐control components of attention (for a review on the relationship of these components with LC‐NE activity, see Bast et al., ), Geva et al. () have described PDil effects related to the attentional and control components of attention that have onset latencies similar to those of the PDil effects observed in our study.…”
Section: Discussionsupporting
confidence: 79%
“…In humans, a combined fMRI/PDil investigation has also highlighted a relationship between PDil and the BOLD activity in a dorsal pontine area that overlaps with the Locus Coeruleus (LC) (Murphy, Robertson, Balsters, & O'connell, ). Taken together, these findings suggest that PDil can be used as a non‐invasive index of LC‐NE activity (for review, see Bast, Poustka, & Freitag, ).…”
Section: Introductionmentioning
confidence: 84%
“…In the brain, NE is synthesized primarily in the locus coeruleus (LC), a small yet powerful nucleus located in the pons. Noradrenergic LC neurons project throughout the brain and exert a wide range of effects, including processing sensory information (Berridge and Waterhouse, 2003), regulating the sleep-wake/arousal state (Berridge et al, 2012), and mediating attentional function (Bast et al, 2018). Blocking noradrenergic transmission causes impaired cognition and arousal and is closely correlated with a variety of psychiatric conditions and neurodegenerative diseases, including stress (Chrousos, 2009), anxiety (Goddard et al, 2010), depression (Moret and Briley, 2011), attention-deficit hyperactivity disorder (ADHD) (Berridge and Spencer, 2016), and Parkinson’s disease (PD) (Espay et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The LC, a noradrenergic "hub" used in the brain as a pacemaker for attentional processes, also controls the muscles in the iris (Laeng et al, 2012), and changes in pupil diameter have been shown to directly correlate with activation changes in LC neurons that signify attentional shifts (Laeng et al, 2012;Rajkowski, Majczynski, Clayton & Aston-Jones, 2004). This psychophysiological signature is also presumed to reveal social processing development and differences, as social perception is a product of attentional shifts due to the prioritized attention placed on social stimuli (Bast, Poustka, & Freitag, 2018). Indeed, it has been shown that infants as young as one month show differential (larger) pupil dilation in response to social vs. non-social stimuli (Fitzgerald, 1968).…”
Section: Introductionmentioning
confidence: 99%